A checklist of nematode parasites from Indonesian murids - Dewi, Kartika; Purwaningsih, Endang (Zootaxa, 2013)
A checklist of nematode parasites from Indonesian murids with their geographic distribution is presented. This checklist is compiled from three sources: the catalogue of nematode parasites of Museum Zoologicum Bogoriense (unpublished specimens in the collection), data from our previous research and articles on nematodes of Indonesian murids. This checklist is presented as a list of nematode parasites with host information, and a host list with information on their nematodes. This paper reports 38 nominal species of nematodes and 13 species identified to the generic level only. The nematodes reported comprise 32 genera and 17 families parasitizing 32 species of Indonesian murids.